2019
DOI: 10.1002/jbt.22308
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA‐3191 promotes migration and invasion by downregulating TGFBR2 in colorectal cancer

Abstract: Mutations in transforming growth factor beta receptor II (TGFBR2) are detected in up to 30% of overall colorectal cancer (CRC). Dysregulation of some microRNAs participated in the CRC pathogenesis. In this study, we used the gene ontology analyses, the Kyoto Encyclopedia of Genes and Genomes pathway analyses and gene set enrichment analysis to indicate that miR-3191 was involved in the regulation of transforming growth factor beta (TGF-BETA) signal pathway in CRC. These bioinformatics results were supported by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 25 publications
1
13
0
Order By: Relevance
“…In addition, bioinformatics analysis predicted TGFBR2 as a potential target gene of miR-23a-3p. Despite little emphasis on TGFBR2 in the literature, its mutation and downregulation was detected in various types of cancer such as colorectal cancer, lung cancer and breast cancer (20,(29)(30)(31)(32). Furthermore, Shima et al (33) reported that mutations in TGFBR2 were associated with 5-year survival rates in colorectal cancer.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, bioinformatics analysis predicted TGFBR2 as a potential target gene of miR-23a-3p. Despite little emphasis on TGFBR2 in the literature, its mutation and downregulation was detected in various types of cancer such as colorectal cancer, lung cancer and breast cancer (20,(29)(30)(31)(32). Furthermore, Shima et al (33) reported that mutations in TGFBR2 were associated with 5-year survival rates in colorectal cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Cell migration ability was evaluated using a previously described wound healing assay (20). After growing the 16HBE cells to 90% confluence in six-well plates, the cell layers were horizontally scraped using a sterile 10 mL pipette tip across the plate.…”
Section: Wound Healing Assaymentioning
confidence: 99%
“…mirnas are rna molecules 21-23 nucleotides in length, which do not encode proteins but regulate gene expression through binding to specific miRNA-binding sites on target mrnas (14,15). mirnas act as biological regulators in a range of cellular processes, such as cell proliferation, invasion and apoptosis or programmed cell death (16,17). notably, mir-374a negatively regulates its downstream genes to control the proliferation and invasion of cancer cells (18).…”
Section: Introductionmentioning
confidence: 99%